Integrated Information System Dashboard for Zero New Stunting Campaign in Kecamatan Cikarang Timur - Tjong Wan Sen; Yosi Yonata (Jurnal Telematika, 2025)
The critical issue of stunting eradication necessitates innovative solutions for effective monitoring, intervention, and prevention. In this paper, we introduce an innovative integrated information system dashboard that leverages the power of data analytics and real-time data processing to provide comprehensive insights into stunting eradication efforts. This assists healthcare providers and policymakers in accessing actionable information crucial for making informed decisions. Our dashboard utilizes digitalization technology to analyze and visualize stunting data in almost real-time, operating nonstop 24/7. This platform enables users to engage in interactive and data-driven decision-making processes. The personalized and user-friendly interface allows for a tailored experience that meets the specific needs and preferences of different stakeholders. We used the Rapid Application Development method with an object-oriented approach to develop this dashboard. We demonstrate the proof of concept of this dashboard through a series of experiments and evaluations. Based on the results of the trial, the designed platform can be very useful for Zero New Stunting campaigns in Kecamatan Cikarang Timur.